The Influence Of Brand And Price On The Purchase Decision Of Sneakers Among Generation Z In Banda Aceh - Juliandi, Nanda; Syahputra, Hendra; Elfida, Cut (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
A purchase decision is an action taken by consumers to purchase a desired product or service. Brand and price are two factors among other factors that can influence purchasing decisions, especially among generation Z. Therefore, it is important to understand the influence of brand and price on purchasing decisions to design effective marketing strategies. Therefore, it is important to understand the effect of brand and price on purchasing decisions to design effective marketing strategies. This study aims to analyze the effect of brand and price on purchasing decisions for sneakers by generation Z in Banda Aceh. This study uses a quantitative approach method with data analysis methods using multiple linear regression. The data collection technique was carried out by distributing questionnaires. The results showed that the brand and price variables had a significant effect on purchasing decisions. Simultaneously, brand and price together have a significant effect on purchasing decisions for sneakers for generation Z in Banda Aceh.